A review on influence of carburizing on ferritic stainless steel. (2020) - Vamshi, Manne; Singh, S.K.; Sateesh, N.; Nagaraju, D.S.; Subbiah, Ram
Abstract: A review is presented on effect of carburizing on ferritic stainless steel and discussed about phase changes, corrosion resistance and mechanical properties. Ferritic steel widely used in many industrial applications. However poor wear resistance, hardness and toughness limits its applications. Ferritic stainless steel contains very low carbon content which subsequently has the properties like ductility, Low strength etc. and chromium inhibits the resistance to corrosion. Carburizing diffuses the carbon on the surface of the AISI 430 FSS which creates the case hardened surface.